EVALUASI SUMUR VERTIKAL DUAL LATERAL TERHADAP PENGARUH KONFIGURASI SUMUR DAN KONSENTRASI SURFAKTAN SERTA PERBANDINGANNYA DENGAN SUMUR HORIZONTAL DAN DUAL LATERAL - Galuh Septyadhi, Rachmat
Selection of Enhanced Oil Recovery method is depends on Recovery Factor (RF). Water and surfactant are usually used to improve recovery factor. The using of horizontal well is suitable for thin reservoir because it has sweep area wider than vertical well. A well with two or more branches joined to a main wellbore is called multilateral well. Dual-lateral well is part of multilateral well and it has recovery higher than recovery of horizontal well in the same of drainage area. Configuration of dual-lateral well should have modified to vertical dual-lateral and evaluated to increase recovery and produce by economical cost. This study is to show that the recovery factor effected by depth of lateral wells, surfactant concentration, the distance between wells and length of lateral wells.The reservoir model is created by a petroleum software, Eclipse.Reservoir produced by one vertical dual-lateral production well and two vertical dual-lateral injection well.Production well located in the middle of injector and they are arranged in paralel. The RF is the best when lateral injection at bottom of reservoir and lateral production at top of reservoir, surfactant concentration is 15 lb/stb, the distance between wells and lateral length is 1100 ft. The result were followed by a study to compare the performance of horizontal, dual-lateral, and vertical dual-lateral well. The results are vertical dual-lateral have RF 0.674% better than horizontal well and 0.597% better than dual-lateral well.